2022
DOI: 10.1212/wnl.0000000000200670
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Patients With Chronic Tension-Type Headache

Abstract: Background and Objectives:Whether acupuncture is effective for chronic tension-type headache (CTTH) is inconclusive. We aimed to examine the effectiveness of acupuncture with a follow-up period of 32 weeks.Methods:We conducted a randomized controlled trial, and 218 participants who were diagnosed with CTTH were recruited from June 2017 to September 2020. The participants in the intervention group received 20 sessions of true acupuncture (TA group) over 8 weeks. The acupuncture treatments were standardized acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Through reading full texts, 26 studies were excluded, and the reasons for exclusion are listed in Appendix 2 . We included an article ( 47 ) as a supplement to Zhang ( 34 ), a total of 30 RCTs ( 21 23 , 27 – 36 , 48 64 ) involving 2,742 participants were included (1,349 in the intervention group and 1,393 in the control group) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through reading full texts, 26 studies were excluded, and the reasons for exclusion are listed in Appendix 2 . We included an article ( 47 ) as a supplement to Zhang ( 34 ), a total of 30 RCTs ( 21 23 , 27 – 36 , 48 64 ) involving 2,742 participants were included (1,349 in the intervention group and 1,393 in the control group) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Melchart and his colleagues concluded that manual acupuncture was better than no treatment in reducing headache frequency of TTH ( 22 ). Zheng et al reported that 8-week acupuncture treatment was effective to alleviate pain intensity in patients with chronic TTH ( 23 ). However, previous systematic reviews and meta-analyses of acupuncture for TTH hold inconsistent results ( 20 , 24 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that significant progress has been made in the field of semantic segmentation [6,7,33,50,53,55,58,60,62], most existing methods focus on the closed-set setting in which dense prediction is performed on the same set of categories in training and testing time. Thus, methods that are trained and perform well in the closed-set setting may fail when applied to the open world, as pixels of unseen objects in the open world are likely to be assigned categories that are seen during training, causing catastrophic consequences in safety-critical applications such as autonomous driving [63]. Straightforward solutions include fine-tuning or retraining the existing neural networks, but it is impractical to enumerate unlimited unseen categories during retraining, let along large quantities of time and efforts needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the study "Acupuncture for Patients With Chronic Tension-Type Headache: A Randomized Controlled Trial," Zheng et al looked at how well acupuncture worked for people with chronic tension-type headaches (TTHs). 1 How Was This Study Done?…”
mentioning
confidence: 99%